Compressive and lap shear tests on traditional putty and polymer sealants. (January 2016) - Lauriks, Leen; Wouters, Ine; Belis, Jan
Abstract: In the 19th century, iron-and-glass roofs were built using linseed oil based putty as sealant to fix the glass plates in the iron glazing bars. Since then, two evolutions influenced the construction details of roofs drastically. First, new sealants with better mechanical properties and higher durability displaced the use of traditional putty. Second, as the insights in the properties and behaviour of glass improved, glass plates can today play a structural role in the global stability of an iron-and-glass structure. This article examines the mechanical properties of the traditional linseed oil based putty to assess the structural integrity of existing iron-and-glass roofs. Single-lap shear and compressive tests are carried out on a traditional linseed oil putty sealant. Next, to determine the impact of a renovation campaign, a modern MS polymer sealant with comparable viscosity and texture but higher durability, is subjected to single-lap shear experiments. The experiments demonstrate that the linseed oil putty can have significant compressive stiffness. However, the shear strength is negligible. The modern polymer sealant has higher shear stiffness and strength as well as a cohesive failure in shear.